2017
DOI: 10.1007/s40257-017-0316-7
|View full text |Cite
|
Sign up to set email alerts
|

Laser and Light Treatments for Hair Reduction in Fitzpatrick Skin Types IV–VI: A Comprehensive Review of the Literature

Abstract: Unwanted facial and body hair presents as a common finding in many patients, such as females with hirsutism. With advances in laser and light technology, a clinically significant reduction in hair can be achieved in patients with light skin. However, in patients with darker skin, Fitzpatrick skin types (FST) IV-VI, the higher melanin content of the skin interferes with the proposed mechanism of laser-induced selective photothermolysis, which is to target the melanin in the hair follicle to cause permanent dest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 37 publications
0
31
0
1
Order By: Relevance
“…In contrast, Nd:YAG laser was associated with lower incidence of hyperpigmentation than IPL but resulted in higher pain scores. Similarly, Fayne et al . reported that laser and IPL are well‐tolerated during and after hair removal in dark skin types, especially after the introduction of laser devices with longer wavelengths and multiple treatment sessions.…”
Section: Discussionmentioning
confidence: 91%
“…In contrast, Nd:YAG laser was associated with lower incidence of hyperpigmentation than IPL but resulted in higher pain scores. Similarly, Fayne et al . reported that laser and IPL are well‐tolerated during and after hair removal in dark skin types, especially after the introduction of laser devices with longer wavelengths and multiple treatment sessions.…”
Section: Discussionmentioning
confidence: 91%
“…This study reports unique aspects of diode laser 805 nm hair removal safety in a mixed-race group of patients and no similar study is found among available references. Available references report that hair removal using diode laser is safe and effective in all skin types according to Fitzpatrick scale, as shown in studies of Cameron et al, 1 Pavlović et al 11 and Fayne et al 2 ; however no study was made in accordance to mixed race patients. In this study, investigators achieved excellent results in pubic area in a group of mixed race patients in objective 86, 90% and subjective 84, 40% assessments.…”
Section: Discussionmentioning
confidence: 99%
“…During the initial consultation, it is necessary to inform the patients about the possible occurrence of side effects as part of the therapy and educate them on all skin care routines that might cause or minimize those side effects. 2,3 Patients may expect redness, skin irritation, erythema, postoperative hypersensitivity and possible burns manifested by blisters and scabs. It is also possible to experience pigmentary changes such as hyperpigmentation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The review of available existing references, including Fayne et al in 2018 18 indicates that diode lasers, alexandrite lasers, Nd:YAG, ruby lasers and some sources of IPL are safe for hair reduction with minimal side effects in groups of IV-VI skin type patients as long as proper treatment protocols and energy settings are used.…”
Section: Discussionmentioning
confidence: 99%